The Use of Zero‐Valent Iron (ZVI) Technology to Promote DDT and Dieldrin Degradation at Point Pelee National Park. Issue 2 (March 2017) - Dahmer, Carolina P.; Rutter, Allison; Zeeb, Barbara A.
Abstract : Point Pelee National Park (PPNP) is highly contaminated with dichlorodiphenyltrichloroethane (DDT) and dieldrin due to the historical use of these two persistent organochlorine pesticides. Zero‐valent iron (ZVI) technology with and without amendments has been successfully used in the past to promote organochlorine pesticides degradation in several locations in North America and Europe. In this study, the use of two commercially available ZVI products, DARAMEND ® and EHC ®, to promote DDT and dieldrin degradation in PPNP's soil and groundwater were investigated. DARAMEND ® was applied to PPNP's soil in a laboratory experiment and in an in situ pilot‐scale plot. In both cases, DARAMEND ® did not significantly increase DDT or dieldrin degradation in treated soils. The effectiveness of EHC ® was tested in a laboratory experiment that simulated the park's groundwater environment using PPNP's pesticide contaminated soil. The result was consistent with the one reported for DARAMEND ®, in that there was no significant increase in DDT or dieldrin degradation in any of the samples treated with EHC ® . These results demonstrate that both of these ZVI commercially available products are not suitable for in situ remediation at PPNP.  ©2017 Wiley Periodicals, Inc.